Testicular disposition of clofarabine in rats is dependent on equilibrative nucleoside transporters. Issue 4 (21st July 2021) - Miller, Siennah R.; Jilek, Joseph L.; McGrath, Meghan E.; Hau, Raymond K.; Jennings, Erin Q.; Galligan, James J.; Wright, Stephen H.; Cherrington, Nathan J.
Abstract: Acute lymphoblastic leukemia (ALL) is the most common cancer in children and adolescents. Although the 5‐year survival rate is high, some patients respond poorly to chemotherapy or have recurrence in locations such as the testis. The blood–testis barrier (BTB) can prevent complete eradication by limiting chemotherapeutic access and lead to testicular relapse unless a chemotherapeutic is a substrate of drug transporters present at this barrier. Equilibrative nucleoside transporter (ENT) 1 and ENT2 facilitate the movement of substrates across the BTB. Clofarabine is a nucleoside analog used to treat relapsed or refractory ALL. This study investigated the role of ENTs in the testicular disposition of clofarabine. Pharmacological inhibition of the ENTs by 6‐nitrobenzylthioinosine (NBMPR) was used to determine ENT contribution to clofarabine transport in primary rat Sertoli cells, in human Sertoli cells, and across the rat BTB. The presence of NBMPR decreased clofarabine uptake by 40% in primary rat Sertoli cells ( p  = .0329) and by 53% in a human Sertoli cell line ( p  = .0899). Rats treated with 10 mg/kg intraperitoneal (IP) injection of the NBMPR prodrug, 6‐nitrobenzylthioinosine 5′‐monophosphate (NBMPR‐P), or vehicle, followed by an intravenous (IV) bolus 10 mg/kg dose of clofarabine, showed a trend toward a lower testis concentration of clofarabine than vehicle (1.81 ± 0.59 vs. 2.65 ± 0.92 ng/mg tissue; p  = .1160). This suggests that ENTs could be important for clofarabine disposition. Clofarabine may be capable of crossing the human BTB, and its potential use as a first‐line treatment to avoid testicular relapse should be considered. Abstract : Proposed mechanism of clofarabine transport across the blood–testis barrier (BTB).